PENINGKATAN HASIL BELAJAR FISIKA MELALUI MODEL DISCOVERY LEARNING MENGGUNAKAN MEDIA POWER POINT PADA SISWA KELAS IX B SMP N 2 SUMBERLAWANG SEMESTER II TAHUN PELAJARAN 2018/2019 - Ninuk Suryani (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This classroom action research was conducted to find solutions to problems faced by class IXB students of SMP N 2 Sumberlawang because of the low student learning outcomes in physics subjects. The purpose of this classroom action research is to find out: 1. how much increase in student learning outcomes through the Discovery Learning model using power point media on magnetism material, 2. the role of the Discovery Learning model using power point media on magnetism material to changes in student learning behavior. This research used a classroom action research type where 31 students of class IXB were given learning treatment through the Discovery Learning model using power point media on magnetism material. Learning outcomes and student learning behavior were analyzed descriptively qualitatively. In this classroom action research, there are 2 cycles, each of which consists of 4 activities, namely: 1. planning, 2. action, 3. observation, 4. reflection. The results of this classroom action research show that: (1) the Discovery Learning model using power point media can improve physics learning outcomes in magnetic materials. This can be seen from the increase in learning outcomes in cycle I to cycle II, namely 73.90 to 75.60, (2) the Discovery Learning model using power point media on magnetic material can change student learning behavior for the better. This can be seen from the increase in teacher observation scores from cycle I to cycle II by 3.57 to 3.64 and an increase in student positive behavior from 66.77% in cycle I to 82.26% in cycle II, as well as a reduction in student negative behavior. from 33.23% in cycle I to 17.74% in cycle II.